Gait Retraining with Realtime Feedback May Reduce Pain and Improve Function in Runners: A Systematic Review - Michael S. Crowell; Jamie B. Morris; Ryan C. Peterson; Michael P. DiLullo; Shane A. McKeon; Cameron S. Young (Journal of Science in Sport and Exercise, 2026)
Purpose Running-related lower extremity injuries are common and often linked to modifiable biomechanical factors. Gait retraining (GR) using real-time feedback (RTF) has emerged as a potential intervention to alter running biomechanics and reduce pain, but the clinical effectiveness in injured runners has not been determined. The purpose of this study was to evaluate the effectiveness of GR with RTF on lower extremity pain and function in runners. Methods A systematic search of 4 databases identified studies involving runners over age 18 with lower extremity pain who received GR with RTF. Studies were assessed for methodological quality using National Institutes of Health Quality Assessment Tools. Results Nine studies met inclusion criteria. There were 5 level II studies (2 good, 2 fair, 1 poor quality) and 4 level IV studies (1 good, 3 fair quality). Two RCTs found significant reductions in pain between groups. Two RCTs found no between-group differences but did report significant improvements within groups. All RCTs and case series showed within-group pain reductions (Visual Analogue Scale decrease range: 2.2–5.0; Numerical Pain Rating Scale: 2.1–5.9). Improvements in self-reported function (Lower Extremity Functional Scale, Anterior Knee Pain Scale) were observed in all 5 studies that measured functional outcomes. Protocols varied but typically involved 8–10 sessions over 4–6 weeks using verbal, visual, or auditory feedback to promote a non-rearfoot strike and increased step rate. Conclusion Low certainty evidence supports GR with RTF to reduce pain in runners. While within-group improvements often exceeded clinically meaningful thresholds, small sample sizes, heterogeneity, and limited high-quality trials constrained definitive conclusions and did not allow for meta-analysis. Larger, methodologically rigorous studies are needed to optimize and validate GR protocols using RTF.